Streptococcus pneumoniae capsular polysaccharide is linked to peptidoglycan via a direct glycosidic bond to β-D-N-acetylglucosamine - Larson, Thomas R. (Proc Natl Acad Sci U S A, 2017)
For many bacteria, including those important in pathogenesis, expression of a surface-localized capsular polysaccharide (CPS) can be critical for survival in host environments. In Gram-positive bacteria, CPS linkage is to either the cytoplasmic membrane or the cell wall. Despite the frequent occurrence and essentiality of these polymers, the exact nature of the cell wall linkage has not been described in any bacterial species. Using the Streptococcus pneumoniae serotype 2 CPS, which is synthesized by the widespread Wzy mechanism, we found that linkage occurs via the reducing end glucose of CPS and the β-D-N-acetylglucosamine (GlcNAc) residues of peptidoglycan (PG). Hydrofluoric acid resistance, (31)P-NMR, and (32)P labeling demonstrated the lack of phosphodiester bonds, which typically occur in PG–polysaccharide linkages. Component sugar analysis of purified CPS–PG identified only CPS and PG sugars in the appropriate ratios, suggesting the absence of an oligosaccharide linker. Time of flight mass spectrometry confirmed a direct glycosidic linkage between CPS and PG and showed that a single CPS repeat unit can be transferred to PG. The linkage was acetolysis susceptible, indicative of a 1,6 glycosidic bond between CPS and the GlcNAc C-6. The acetylation state of GlcNAc did not affect linkage. A direct glycosidic linkage to PG was also demonstrated for serotypes 8 and 31, whose reducing end sugars are glucose and galactose, respectively. These results provide the most detailed descriptions of CPS–PG linkages for any microorganism. Identification of the linkage is a first step toward identifying the linking enzyme and potential inhibitors of its activity.